Fusion of intra- and extracellular forms of vaccinia virus with the cell membrane. - Doms, R W (1990)
The membrane fusion activities of the isolated single-envelope intracellular form of vaccinia virus (INV) and the double-envelope extracellular (EEV) form were studied by using a lipid-mixing assay based on the dilution of a fluorescent probe. Fluorescently labeled INV and EEV from both the IHD-J and WR strains of vaccinia virus fused with HeLa cells at neutral pH, suggesting that fusion occurs with the plasma membrane during virus entry. EEV fused more efficiently and with faster kinetics than INV: approximately 50% of bound EEV particles fused over the course of 1 h, compared with only 25% of the INV particles. Fusion of INV and EEV was strongly temperature dependent, being decreased by 50% at 34 degrees C and by 90% at 28 degrees C. A monoclonal antibody to a 14-kilodalton envelope protein of INV that has been implicated in the fusion reaction (J. F. Rodriguez, E. Paez, and M. Esteban, J. Virol. 61:395-404, 1987) completely suppressed the initial rate of fusion of INV but had no effect on the fusion activity of EEV, suggesting that vaccinia virus encodes two or more membrane fusion proteins. Finally, cells infected with the WR strain of vaccinia virus formed syncytia when briefly incubated at pH 6.4 or below, indicating that an acid-activated viral fusion protein is expressed on the cell surface. However, WR INV and EEV did not display increased fusion activity at acid pH, suggesting that the acid-dependent fusion factor is not incorporated into virions or that its activity there is masked.